Alzheimer's and other dementias - Hughes, Julian C. (Facts (Oxford, England), 2011)
With more people in the world living into older age, Alzheimer's and other Dementias: The Facts takes a comprehensive look at the spread of dementia, and provides authoritative information and practical advice for sufferers, their families, and the medical professionals who care for them. Written by a consultant in old age psychiatry, the book provides an overview of all the different types of dementia (including younger-onset dementias), from the most-recognized - Alzheimer's - to the less-frequent types, such as those caused by inherited metabolic disorders or HIV. The book guides the reader step-by-step through how the brain works, and explains in clear and simple language the effect of dementias on the brain, and the impact on an individual's cognitive function. A dedicated chapter explains how a diagnosis is reached, including the different modes of assessment, from blood tests carried out by a GP, to specialist scans, highlighting how the brain actually works. Detailed sections cover the latest treatments available, including the controversial use of antipsychotic medication, and the possibility of disease-modifying treatments in the future. The book also explains how the multi-disciplinary team works together to look after the sufferer's social needs, such as bathing and washing, as well as their spiritual and palliative needs. Alzheimer's and other Dementias: The Facts provides all the relevant information and guidance for sufferers, family and their care-givers to choose the right intervention at the right time, to create - as the book advocates - a unique and personalized management plan.